Contributions of science to competitive judo - Fernandes Monteiro, L.; Garcia Garcia, J. M. (The Arts and Sciences of Judo, 2024)
This study examines the contributions of science to competitive judo, focusing on the evolution of training methods and the role of technology in enhancing performance. The integration of scientific principles has revolutionised traditional training practices, with advancements in biomechanics, physiology and data analytics enabling a more pre-cise understanding of athlete preparation and performance. Ergogenic aids, including nutritional interventions, reco-very techniques and wearable technologies, are explored as key innovations that have reshaped the way judoka train and compete. By bridging the gap between traditional judo practices and modern scientific approaches, this research highlights the transformative impact of science and technology on competitive judo.